Evaluation of future teachers’ project activity through the use of information and communication technologies (Intel Program «Education for the Future») (Pedagogy of Higher and Secondary Education, 2014)
Kucher S. L. Evaluation of future teachers’ project activity through the use of information and communication technologies (Intel Program «Education for the Future»).The article examines possibilities of applying Intel Program «Education for the Future in Ukraine» in evaluating results as for creative designing of future teachers of technologies.
Keywords: information and communication technologies (ICT); evaluations; technological education; educational projects; Intel educational programs